FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BIDAN DI KABUPATEN BONE BOLANGO PROPINSI GORONTALO - Patabuga, Sunarti (Jurnal Sainstek, 2010)
The purpose of this research is to know factors influencing the performance of midwives in Bone Bolango Regency in 2010. The type of this research is quantitative with cross sectional approach. The samples of this research were all midwives both goverment employees and temporary employees in Bone Bolango Regency using 58 samples. The date were analyzed by using SPSS with chi square test and logistic regression. The result show that there are influences between age, motivation, family, organization, superviision and career development on midwives performance. Supervision constitutes the most influential variable on midwives performance. Keyword : Midwifes, performance